Elimination of impurity phase formation in FePt magnetic thin films prepared by pulsed laser deposition - Wang, Ying (2014)
The formation of impurity phases in FePt thin films severely degrades its magnetic properties. The X-ray diffraction patterns of FePt thin films, synthesized using pulsed laser deposition (PLD), showed peaks corresponding to impurity phases, resulting in softer magnetic properties. A systematic investigation was carried to determine the factors that might have led to impurity phase formation. The factors include (i) PLD target composition, (ii) substrate material, (iii) annealing parameters such as temperature, duration and ambience and (iv) PLD deposition parameters such as chamber ambience, laser energy fluence and target–substrate distance. Depositions on the different substrates revealed impurity phase formation only on Si substrates. It was found that the target composition, PLD chamber ambience, and annealing ambience were not the factors that caused the impurity phase formation. The annealing temperature and duration influenced the impurity phases, but are not the cause of their formation. A decrease in the laser energy fluence and increase of the target–substrate distance resulted in elimination of the impurity phases and enhancement in the magnetic and structural properties of FePt thin films. The energy of the ablated plasma species, controlled by the laser energy fluence and the target–substrate distance, is found to be the main factor responsible for the formation of the impurity phases.